Landscape-scale vegetation patterns influence small-scale grazing impacts. (December 2015) - Moore, Emily K.; Britton, Andrea J.; Iason, Glenn; Pemberton, Josephine; Pakeman, Robin J.
Abstract: Understanding the distribution of herbivory is of great importance to planning the conservation management of plant communities. Control of wild and domestic large herbivore populations at large scales is commonly used to manipulate their impacts. However, the relationship between large scale population density and local impacts is often weak as the spatial layout of plant communities, and the herbivores' preferences for them, can drive the herbivores' habitat use. We tested the effects of proximity of a preferred plant community at scales up to 3 km 2 on the grazing impact of red deer ( Cervus elaphus ) on four plant communities of conservation importance. We also tested the relationship between grazing impacts and herbivore density at the scale of deer management units on the site. Grazing impact was measured using direct and indirect indicators of grazing. The area of the preferred species-rich grassland in proximity to the target site influenced grazing impacts on both preferred (grassland) and less-preferred (heath) communities. Grazing impacts on heaths were higher when there was more species-rich grassland present within 1000 m. Grazing impacts on species-rich grasslands were lower when the area of species-rich grassland within 500 m was small, especially when there was also more species-rich grasslands in the wider area (500–1000 m away). Herbivore density was only weakly correlated to grazing impacts. Where plant communities with contrasting grazing sensitivity to or requirement for grazing to maintain them exist side by side, there is an inherent conflict in managing for the conservation of both. Our understanding of the role of spatial layout of adjacent communities as a determinant of herbivore impact may inform the management and prioritisation of the conservation of one plant community over others. Highlights: We studied the effect of deer density and plant community mosaic on grazing impact. Deer density explained little variation in grazing impact. On heaths, grazing impact was higher when there was extensive grassland within 1 km. Isolated grasslands experienced lower grazing impacts. There are trade-offs in managing plant community mosaics with herbivores.